In Vitro Gibberellin A(4) Binding to Extracts of Cucumber Hypocotyls - Keith, Brian (1981)
Cucumber hypocotyls were extracted and the extract centrifuged at 100,000g to yield a supernatant or cytosol fraction. Binding of [(3)H]-gibberellin(4) (GA(4)) to soluble macromolecular components present in the cytosol was demonstrated at 0 C by Sephadex chromatography. Binding assays performed with cytosol that had been preheated or incubated with protease, DNase, RNase, or phospholipase A or C indicated that heat and protease treatments disrupted the binding, which suggests that binding occurred to a protein. Equilibrium dialysis of a protein-enriched fraction prepared by ammonium sulfate precipitation also indicated binding of [(3)H]GA(4) to macromolecular components. [(3)H]GA(4) binding was pH-sensitive, saturable, reversible, and significantly affected by biologically active gibberellins, but not by inactive gibberellins or other plant hormones such as indoleacetic acid, abscisic acid, or kinetin. Thin layer chromatography indicated that [(3)H]GA(4), and not a metabolite, was the species bound. A kinetic analysis indicated that specific binding of [(3)H]GA(4) was due to a single class of binding sites having an estimated K(d) of 10(−7) molar and a concentration of 0.8 × 10(−12) moles gram(−1) fresh weight or 0.4 × 10(−12) moles milligram(−1) soluble protein.